Abdominal emergency related to retro and intraperitoneal lesions caused by COVID-19 - Njoumi, Noureddine; Kasouati, Jalal; Zentar, Aziz; Ali, Abdelmounaim Ait (International Surgery Journal, 2021)
Digestive manifestations accompanying or preceding respiratory symptoms of coronavirus disease (COVID-19) caused by severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) are frequent and appears to be associated with its most severe forms. In contrast, isolated digestive involvement in covid-19 is rare and misdiagnosed. It was found that nausea/vomiting, diarrhea, abdominal pain and loss of appetite are the main recognized digestive disorders in patients infected by SARS-COV-2. Acute abdomen with occlusive syndrome has never been reported in the literature to our knowledge. We report the case of a 60-year-old woman who was presented with an occlusive syndrome related to retro and intraperitoneal lesions caused by Covid-19 infection without any respiratory manifestations. She underwent an emergency surgery. The paucity of data about this unusual clinical presentation posed a serious diagnostic and therapeutic challenge.